Damage formations of ramie fiber composites multilayer armour system under high-velocity impacts - Mujiyono; Nurhadiyanto, Didik; Mukhammad, Alaya Fadllu Hadi; Riyadi, Tri Widodo Besar; Wahyudi, Kristanto; Kholis, Nur; Wulandari, Asri Peni; Hassan, Shukur bin Abu (Eastern-European Journal of Enterprise Technologies, 2023)
Multilayer armour system (MAS) becomes the best choice in reinforcing protection for military officers against projectile attack which has a high velocity of up to 7.62×51 mm NATO ball lead core (projectile level III NIJ standard) or AP 7.62×51 mm hard steel core (projectile level IV NIJ standard). This study aimed to analyze the damage formation of wolfram carbide (WC) ceramic and ramie fiber composites. The frontmost MAS uses WC ceramic and is enveloped by a back layer of ramie fiber composites with epoxy resin reinforcing material as the matrix. Ballistic testing was carried out in this study using a long-barreled rifle to determine the resistance of the MAS from projectile impact. The speed meter in ballistic testing uses a velocity sensor type light screen B 471 and clay witness is used to measure back face signature (BFS). The results show that 7.62 lead core and hard steel core projectiles were unable to penetrate the 3-layer ceramic MAS in the front. The results are marked by a relatively low BFS value of 1.45 and 1.17 mm, so that the energy in the MAS with 3 ceramic layer is absorbed efficiently but with the phenomenon of rupture ceramic failure. Ceramic rupture failure needs to be overcome by bonding several layers of ramie so that MAS can be used in the next stage. MAS with 1 and 2 ceramic layers are unable to withstand projectile level III and level IV NIJ standard. From these results it is known that the MAS limit can withstand the projectile level III and IV NIJ standard, namely MAS with 3 ceramic layers. The damage formation of ceramic was rupturing ceramic failure. Therefore, it is necessary to design a ceramic binder by placing some ramie fibers in front of the ceramic